1997
DOI: 10.1111/j.1540-6288.1997.tb00912.x
|View full text |Cite
|
Sign up to set email alerts
|

The Causality Effects of the Federal Reserve's Monetary Policy on U.S. and Eurodollar Interest Rates

Abstract: Previous studies argue that U.S. interest rates will become more sensitive to changes in eurodollar rates as international financial-market integration increases. However, the empirical results of these studies are suspect because they select their subperiods in an ad hoc manner and ignore the different trading hours of the U.S. and London markets.This study adjusts for the markets' different trading hours and uses Goldfeld and Quandt's switching regression technique to show that the causal relation between U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 10 publications
(20 reference statements)
0
19
2
Order By: Relevance
“…Mougoue and Wagster (1997) found bidirectional causality between the US and Eurodollar interest rates during 1973-1979, unidirec-tional causality from the Eurodollar rate to the US domestic rate during [1979][1980][1981][1982], and reverse unidirectional causality from the US domestic rate to the Eurodollar rate during 1982-1992. Similarly, Clinebell et al (2000 found unidirectional causality running from the US interest rate to the offshore LIBOR rate under the regime of borrowed reserves targeting.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Mougoue and Wagster (1997) found bidirectional causality between the US and Eurodollar interest rates during 1973-1979, unidirec-tional causality from the Eurodollar rate to the US domestic rate during [1979][1980][1981][1982], and reverse unidirectional causality from the US domestic rate to the Eurodollar rate during 1982-1992. Similarly, Clinebell et al (2000 found unidirectional causality running from the US interest rate to the offshore LIBOR rate under the regime of borrowed reserves targeting.…”
Section: Introductionmentioning
confidence: 82%
“…Similarly, Clinebell et al (2000 found unidirectional causality running from the US interest rate to the offshore LIBOR rate under the regime of borrowed reserves targeting. Furthermore, both Mougoue and Wagster (1997) and Clinebell et al (2000) argued that the evidence of unidirectional causality running from the US interest rate to the offshore rate did not support the argument of increasing financial market integration over time.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is expected that financial services firms, particularly mutual fund companies and brokers, would be adversely affected by an unexpected monetary tightening that made investing in stock funds less attractive. In terms of financial institutions, Mougoue and Wagster (1997) found that bank deposit rates are significantly affected by monetary policy. A monetary policy tightening can be expected to raise the cost of borrowed reserves and decrease the supply of loans therefore placing upward pressure on lending rates.…”
Section: Macroeconomic Variables and Financial Sector Stock Returnsmentioning
confidence: 98%